If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = 3f Solving 15 = 3f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-3f' to each side of the equation. 15 + -3f = 3f + -3f Combine like terms: 3f + -3f = 0 15 + -3f = 0 Add '-15' to each side of the equation. 15 + -15 + -3f = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -3f = 0 + -15 -3f = 0 + -15 Combine like terms: 0 + -15 = -15 -3f = -15 Divide each side by '-3'. f = 5 Simplifying f = 5
| 63=9x-9 | | 64/27-3(1) | | 67-5x=4x+7 | | 3c+4c= | | 3.3x+159(.167)=1000 | | 10-2*x= | | 9(9)+4y=52 | | 0=2x^2+x-6 | | 3x+4=5(x+1)-3(x+2) | | 4a^2+15a-4= | | 7(2b-5)-(6-5b)=-41 | | 5x+10-30-45+15=360 | | 9(4)+4y=52 | | 18=z+11 | | 4x^2-15x=4 | | X+4(14)=51 | | 5x/7-8=8 | | x+(1/2)x+(1/3)x=60 | | 9x-5*9=-9 | | -3x^2+6x+8=0 | | 17+-3p+4=-7 | | 9x-5*9=9 | | -3(14)+5y=85 | | 4x-5=5x-2x | | -3(2)+5y=85 | | 4m+15=78 | | -3(5)+5y=85 | | 2-x=6x+2 | | -3(8)+5y=85 | | y=4+-8 | | f(x)=2x^3+x^2-8x-4 | | -5(3t-3)+8t=4t-8 |